2018
DOI: 10.1038/s41408-018-0153-9
|View full text |Cite
|
Sign up to set email alerts
|

Next generation flow for minimally-invasive blood characterization of MGUS and multiple myeloma at diagnosis based on circulating tumor plasma cells (CTPC)

Abstract: Here, we investigated for the first time the frequency and number of circulating tumor plasma cells (CTPC) in peripheral blood (PB) of newly diagnosed patients with localized and systemic plasma cell neoplasms (PCN) using next-generation flow cytometry (NGF) and correlated our findings with the distinct diagnostic and prognostic categories of the disease. Overall, 508 samples from 264 newly diagnosed PCN patients, were studied. CTPC were detected in PB of all active multiple myeloma (MM; 100%), and smoldering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
133
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(142 citation statements)
references
References 75 publications
(100 reference statements)
4
133
4
1
Order By: Relevance
“…In contrast, CTPC might not only reflect tumor load but, particularly, the ability of persisting tumor cells to disseminate the disease and support tumor growth and progression at (multiple) distant sites in BM and other tissues, as previously suggested 16 based on their more immature and prominent stem cell-like PC features compared with (paired) BM-derived tumor-plasma cells (TPC). 3 Despite all of this, every CTPC 1 case in our cohort was BM MRD 1 , suggesting that the presence of blood CTPC after therapy might be a surrogate marker of persistent BM MRD in guiding (eg, avoiding) subsequent (more invasive) BM aspiration procedures, particularly among sCR/CR patients. In contrast, a significant fraction of our CTPC 2 cases were BM MRD 1 and/or sIF 1 , supporting the notion that MM is a BM disease with greater levels of infiltration by (usually) functional PC in BM vs PB.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…In contrast, CTPC might not only reflect tumor load but, particularly, the ability of persisting tumor cells to disseminate the disease and support tumor growth and progression at (multiple) distant sites in BM and other tissues, as previously suggested 16 based on their more immature and prominent stem cell-like PC features compared with (paired) BM-derived tumor-plasma cells (TPC). 3 Despite all of this, every CTPC 1 case in our cohort was BM MRD 1 , suggesting that the presence of blood CTPC after therapy might be a surrogate marker of persistent BM MRD in guiding (eg, avoiding) subsequent (more invasive) BM aspiration procedures, particularly among sCR/CR patients. In contrast, a significant fraction of our CTPC 2 cases were BM MRD 1 and/or sIF 1 , supporting the notion that MM is a BM disease with greater levels of infiltration by (usually) functional PC in BM vs PB.…”
mentioning
confidence: 78%
“…Recent large-scale genome-sequencing studies using bone marrow samples have demonstrated that most cases of MDS and other related neoplasms, such as acute myeloid leukemia and myelodysplastic/myeloproliferative neoplasm overlap syndromes, harbor pathogenic somatic mutations in diverse myeloid cancer driver genes. [2][3][4][5][6] Moreover, some or all of these mutations can be detected in PB granulocytes in most patients with MDS and related neoplasms (Phillip D. Michaels, Dahai Wang, A.S.K., manuscript in preparation). 7,8 Despite these advances and the widespread use of NGS testing, there are limited data on the clinical use of NGS testing in the early evaluation of patients with cytopenia(s).…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…The prognostic significance of cPCs when measured by MFC has been well established across the spectrum of plasma cell disorders, such as MGUS, smoldering myeloma, MM and AL amyloidosis, at the time of diagnosis. It has also been established as a prognostic marker in MM patients undergoing ASCT by predicting for early relapse .…”
Section: Discussionmentioning
confidence: 99%